Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan Pada PT Pos Indonesia Unit Banjar - Arif Taufikurohman; Aprilia Puspasari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted to determine the impact of compensation and motivation on employee performance at PT Pos Indonesia Banjar Unit. PT Pos Indonesia Banjar Unit faces problems related to employee performance that is not optimal due to a disproportionate compensation system and lack of motivation among employees. In this study, the approach used is a survey with a quantitative method that covers the entire population of 37 employees of PT Pos Indonesia Banjar Unit through a saturated sampling technique to evaluate the effect of compensation and motivation on employee performance. Data were processed using SPSS through several stages, including data quality testing (validity and reliability), classical assumption testing (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing using partial t-test, simultaneous F-test, and coefficient of determination test to analyze the impact of motivation and compensation on employee performance. The findings of this study indicate that compensation has a partially significant positive impact on employee performance, motivation also has a partially significant positive effect on employee performance, and simultaneously, compensation and work motivation have a significant effect on employee performance at PT Pos Indonesia Banjar Unit. Companies are advised to assess the compensation system to ensure it is in line with the workload, improve motivation programs through awards and open comm.unication, and develop training to increase employee independence and initiative in carrying out tasks